Analisis Faktor Resiko Hipertensi Sekunder pada Pengguna Kontrasepsi Aktif di Puskesmas Tanjung Agung Kabupaten Ogan Komering Ulu Sumatera Selatan - Suryanda Suryanda (Jurnal Kesehatan, 2017)
Each year, hypertension causes 1 of 7 deaths worldwide and causes heart, eye, brain, and kidney damage. In addition to smoking, the use of pill contraceptives is one of the risk factors for hypertension. This study aimed to analyze the risk factors of secondary hypertension in active contraceptive users in Tanjung Agung Public Health Center with the analytical descriptive using cross-sectional method. The population was active women using active contraceptives who come to Public Health Center period September-December 2016, amounting to 45 people. The data was taken using the questionnaire in the form of a checklist and open question. The age of respondents in the range of 18 years to 47 years, active contraceptive users with the highest group of varieties were 3-4 children 15 respondents (33.3%), the lowest group >5 children 3 respondents (6.7%). The group was exposed to cigarette smoke 26 respondents (57.7%), the group was not exposed 19 respondents (42.2%). Respondent hypertension 14 respondents (31,1%), which is not hypertension 31 respondent (68,9%). Usage Hormonal contraceptives more, ie 23 respondents (51.1%) than non-hormonal, ie 22 respondents (48.9%). There was a significant correlation between hormonal contraception use and hypertension incidence, with p-value 0,001. There was no significant relationship between exposure to cigarette smoke to contraceptive users with hypertension incidence, p-value 0,057. The need for PHBS education concerning exposure to cigarette smoke and the danger of hypertension to the community.